Demographics, treatment patterns, and healthcare utilization and cost of repository corticotropin injection in patients with systemic lupus erythematosus or rheumatoid arthritis. (2nd November 2017) - Wu, Bingcao; Deshpande, Gaurav; Gu, Tao; Popelar, Breanna; Philbin, Michael; Wan, George J.
Abstract: Objective: To evaluate healthcare resource utilization (HRU) and costs among patients who initiated repository corticotropin injection (RCI; H.P. Acthar Gel) treatment for rheumatoid arthritis (RA) or systemic lupus erythematosus (SLE). Methods: Patients aged ≥18 years with ≥2 diagnoses for either RA or SLE between July 1, 2006 and April 30, 2015 were identified in the HealthCore Integrated Research Database. Index RCI date was the earliest date of a medical or pharmacy claim for RCI after diagnosis. Baseline characteristics, pre- and post-initiation HRU and costs were assessed using descriptive statistics. Results: This study identified 180 RA patients (mean age = 60 years, 56% female) and 29 SLE patients (mean age = 45 years, 90% female) who initiated RCI. First RCI use averaged 7.1 and 22.6 months after the initial RA and SLE diagnosis, respectively. After RCI initiation, RA patients incurred significantly lower per-patient-per-month (PPPM) all-cause medical costs ($1, 881 vs $682, p  < .01) vs the pre-initiation period, driven by lower PPPM hospitalizations costs ($1, 579 vs $503, p  < .01). Overall PPPM healthcare costs were higher ($2, 751 vs $5, 487, p  < .01) due to higher PPPM prescription costs ($869 vs $4, 805, p  < .01). Similarly, SLE patients had decreased PPPM hospitalization costs ($3, 192 vs $799, p  = .04) and increased PPPM prescription costs ($905 vs $7, 443, p  < .01) after initiating RCI; the difference in overall PPPM healthcare costs was not statistically significant likely, due to small sample size. Conclusion: This study, across a heterogeneous population of variable disease duration, described clinical and healthcare utilization and costs of RA and SLE patients initiating RCI in a real-world setting. We observed that patients receiving RCI had lower utilization and costs for medical services in both disease populations, which partially offset the increased prescription costs by 30% and 37%. Future research is needed to explore factors associated with RCI initiation and its impact on long-term outcomes.